Effects of vitamin D deficiency on the improvement of metabolic disorders in obese mice after vertical sleeve gastrectomy - Jie Zhang (Nature Portfolio, 2021)
Abstract Vertical sleeve gastrectomy (VSG) is one of the most commonly performed clinical bariatric surgeries for the remission of obesity and diabetes. Its effects include weight loss, improved insulin resistance, and the improvement of hepatic steatosis. Epidemiologic studies demonstrated that vitamin D deficiency (VDD) is associated with many diseases, including obesity. To explore the role of vitamin D in metabolic disorders for patients with obesity after VSG. We established a murine model of diet-induced obesity + VDD, and we performed VSGs to investigate VDD's effects on the improvement of metabolic disorders present in post-VSG obese mice. We observed that in HFD mice, the concentration of VitD3 is four fold of HFD + VDD one. In the post-VSG obese mice, VDD attenuated the improvements of hepatic steatosis, insulin resistance, intestinal inflammation and permeability, the maintenance of weight loss, the reduction of fat loss, and the restoration of intestinal flora that were weakened. Our results suggest that in post-VSG obese mice, maintaining a normal level of vitamin D plays an important role in maintaining the improvement of metabolic disorders.